Growth of Gyrinops verstegii Seedling in Response to Thinning and Foliar Fertilization - Albert Husein Wawo; Ning Wikan Utami; Ninik Setyowati (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
Gyrinops verstegii is one of agarwoods species, plant with high economic value. However, it is categorized as plant with high risk of extinction, hence it required conservation. This research aimed to examine the effect of thinning and foliar fertilization of G. verstegiiseedling to support its conservation. The study was conducted for 6 months in the glass house of Research Center for Biology, LIPI, at Cibinong Science Center. It was arranged in Factorial Design with two factors and repeated 3 times. The first factor was two thinning treatments (branches prunning): no thinning (P0) and thinning (P1). The second factor was 4 dosages of foliar fertilization : without fertilizer (D0), fertilizer dosages 1 g.l-1 (D1), 2 g.l-1 (D2) dan 3 g.l-1 (D3). Thinning treatment was able to stimulate seedling height and number of seedling branches but inhibited stem diameter as well as foliar fertilization at 2 g.l-1.Thinning and foliar fertilizing at 2 g.l-1 indicated significant effect on height and number of seedling branches but inhibited stem diameter of G. verstegii seedlings.